The Oxford handbook of fiduciary law - Criddle, Evan J. ca. 20./21. Jh; Miller, Paul B. 1977-; Sitkoff, Robert H. 1974- (Oxford handbooks online, 2019)
The Oxford Handbook of Fiduciary Law provides a comprehensive overview of critical topics in fiduciary law and theory through chapters authored by leading scholars. The Handbook opens with surveys of the many fields of law in which fiduciary duties arise. Drawing on these surveys, the Handbook offers a synthetic analysis of fiduciary law's key concepts and principles. Chapters in the volume explore the defining features of fiduciary relationships, clarify the distinctive fiduciary duties that arise in these relationships, and identify the remedies available for breach of fiduciary duties. The Handbook also provides numerous comparative perspectives on fiduciary law from eminent legal historians and from scholars with deep expertise in a diverse array of the world's legal systems